Optimization of human semen analysis using CASA-Mot technology. (4th March 2023) - García-Molina, Almudena; Navarro, Nuria; Valverde, Anthony; Sadeghi, Sara; Garrido, Nicolás; Soler, Carles
Abstract: The purpose of this study is to investigate the optimal framerate (FR) and the use of different counting chambers for improving CASA-Mot technology use in Andrology. Images were captured at 500 fps, then segmented and analyzed in several ranges of FRs (from 25 to 250) to define the asymptotic point that as an optimal FR. This work was replicated using counting chambers based in capillarity (disposable) or drop displacement (reusable) to study their effects on the motility results and kinematic values of the samples under the different experimental conditions. The α value (asymptote corresponding to FRo ) of the exponential curve was 150.23 fps, corresponding to a VCL of 130.58 mm/s, far from the value of 98.89 mm/s corresponding to 50 fps (the highest FR used by most current CASA-Mot systems). Our results have shown that, when using reusable counting chambers, type and depth have influence. In addition, different results were obtained depending on the area of image captured inside the different counting chamber types. To have reliable results in human sperm kinematic studies, almost 150 fps should be used for capturing and analyzing and differences between chambers should be considered by sampling from different areas, to obtain a representative value of the whole sample.